Multitafsir UU ITE Sebagai Koridor Hukum: Studi Pada Intensitas User Conflicts di Media Sosial - Marpaung, Hery Wahyudi; Sazali, Hasan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study aims to examine the impact of multiple interpretations of articles in the Electronic Information and Transaction Law (ITE Law) on the intensity of conflicts between social media users. This study is motivated by the rise of legal cases that arise due to subjective interpretations of Article 27 paragraph (3) and Article 28 paragraph (2), which often lead to the criminalization of legitimate expression in the digital space. Using a qualitative method with a case study approach, data was collected through observation and documentation of digital conflict cases. The results of the study show that the multiple interpretations of these articles not only interfere with legal certainty, but also worsen the psychological condition of users and create inequality in law enforcement. This study also found that low digital literacy and the use of articles as a tool of repression also strengthen the escalation of conflicts on social media. Therefore, a participatory and contextual revision of the ITE Law is needed to ensure fair legal protection, while maintaining freedom of expression in the digital era. The conclusion of this study emphasizes the importance of establishing a digital legal corridor that is adaptive, inclusive, and in harmony with the communication dynamics of modern society in order to create a healthy, safe, and democratic public space.